Semantik dalam Terjemahan: Tantangan dan Strategi dalam Mempertahankan Makna Asli - Kusnadin, Sahdatul Aini; Musdalipa; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article explores the role of semantics in translation, highlighting the challenges and strategies used by translators to maintain the meaning accuracy of the source text. As a branch of linguistics that focuses on meaning, semantics plays a crucial role in translation, given that each language has its own unique meaning system, which is influenced by cultural factors, language structure, and social context. This research uses a literature review and descriptive qualitative approach to examine the semantic theory proposed by Abdul Chaer as well as the translation strategies developed by Mona Baker. A number of challenges in translation are identified, including cultural differences, ambiguity in language, and the difficulty of directly translating idioms and metaphors. In addition, the article also underlines the significance of the dynamic equivalence theory introduced by Eugene A. Nida, which emphasizes that the translation should be able to impact the meaning equivalent to the original text in the source language. Therefore, an in-depth understanding of semantics and cultural aspects is necessary to improve translation accuracy, so that the message of the original text can be effectively conveyed to target language readers.